Improving gait in cerebral palsy : effects of a combined strength, flexibility and gait training Intervention on lower limb gait kinematics and kinetics in children and young adults with spastic cerebral palsy - Thamm, Antonia (2021)
INTRODUCTION. Walking ability is a fundamental skill enabling participation and independence. For people with cerebral palsy (CP) gait can be impaired due to altered musculoskeletal development resulting from a lesion of the developing brain. Neuromuscular impairments like muscle weakness, impaired motor control and reduced range of motion (ROM) are commonly targeted with physical therapy. However, a lack of consistent improvements in motor function requires the development of more evidence-based training interventions to optimally target rehabilitation in CP. The purpose of this thesis is to investigate the effects of a three-month long tailored exercise intervention including strength, flexibility and gait training on lower limb gait kinematics and kinetics, walking endurance and motor function in children and young adults with CP. METHODS. Seventeen children and young adults with spastic CP (9-22 years, 5 bilateral/13 unilateral, 13/5 GMFCS I/III) participated in two to three individually guided 90 minutes sessions and ten minutes of daily walking on an inclined treadmill at home for twelve weeks. 3D lower limb kinematics and kinetics (Vicon) and six minutes walking test (6MWT) performance were assessed twice before and twice after the intervention in intervals of three months. Gross Motor Function Measure (GMFM) was assessed directly pre and post the intervention. The guided intervention sessions consisted of flexibility, strength and treadmill gait training. Seventeen age and sex matched typically developing (TD) control participants were measured once without participation in the intervention. RESULTS. CP participants displayed significantly decreased dorsiflexion (DF) during swing and initial contact, reduced ROM of the knee and hip during stance and smaller peak ankle push-off power compared to the control group. There was no statistically significant change in gait kinematics or kinetics in CP after the intervention. Furthermore, there was no statistically significant increase in distance walked in the 6MWT or GMFM score after the intervention. DISCUSSION. A twelve-week combined strength, flexibility and gait training intervention in children and young adults with CP did not improve gait kinematics or walking function. Despite a lack of significant group effects, analysis of GMFM scores indicated the existence of several responders with clinically relevant improvements in gross motor function. Further studies are needed to investigate the underlying mechanisms behind responders and non-responders to exercise interventions.